Literary translation as an act of mediation between author and reader - Núñez, Kenneth Jordan (Estudios de Traducción, 2012)
In this article, the translation process of literary works is examined from the point of view of functionalism and Skopos theory. The aim is to analyse to what extent the elements intervening in the act of communication (author, reader and situational context) condition that result. On the one hand, the author seeks to prove the hypothesis that states that the translation of a literary work can only be considered “functionally valid” if the message is adequately transmitted and, therefore, if the communicative purpose is met. On the other hand, he considers the possibility that the translation of a literary work may lose validity and that there exists an infinite number of functionally valid translation results, since the elements of communication are different in each particular act.